Education, Expertise, Experience and the Making of Hospital Workers in Canada, 1920-1960 - Twohig, Peter (Scientia Canadensis, 2006)
AbstractBeginning in the 1920s, many Canadian hospitals underwent an extensive period of modernization. A wide variety of workers, generally termed "allied health professionals," began to work alongside physicians and nurses. This paper examines the history of two such groups, x-ray and laboratory technicians, paying particular attention to the ways in which technical education was transformed and, through this transformation, new occupational identities forged. Initially, those who staffed the laboratory and x-ray departments were given quick, practical instruction. In many cases, these workers continued to work in various settings across the hospital. The informal instruction of the 1920s and 1930s was displaced by formal, accredited training programs, replete with national examinations linked to a practice registry in the 1940s. Hospital administrators, the Canadian Medical Association and technicians themselves were all engaged in this transformation. At the same time, national organizations such as the Canadian Society of Laboratory Technologists or the Canadian Society of Radiological Technicians, founded in the late 1930s and early 1940s respectively, attempted to create a common professional identity with a clear scope of practice. Despite this, technical workers' professional identity remained malleable and highly dependent upon context long after the creation of supposedly national accreditation standards.